The US perspective on e-cigarettes and harm reduction - Zeller, Mitch (Journal of Health Inequalities, 2024)
The reality of the nicotine marketplace in US is that today, unlike 60-70 years ago, nicotine can be delivered without having to burn tobacco leaves and inhale the tobacco smoke. And that’s significant because while there are misperceptions about the safety of nicotine, the reality is that nicotine does not directly cause the cancer, the lung disease and the heart disease associated with the use of cigarettes and other combustible products. Now nicotine doesn’t get off the hook entirely, because of course there’s the potential for addiction. And then when we start thinking about the role of flavors and attracting young people to experiment with tobacco products, the potential for nicotine addiction is a real concern. There are also a lot of unanswered questions about something that we call dual use. The great benefit of any of these alternative products is if a smoker completely substitutes all of their cigarettes for an e-cigarette or a heated tobacco product or smokeless tobacco product. But dual use is that pattern of use where the health concerned smoker, rather than stopping to smoke completely, continues to smoke while also using one or more of these other products.